A new species of Brachypogon (Isohelea) from arid zones of Argentina (Diptera: Ceratopogonidae) - Spinelli, Gustavo R.; Cazorla, Carla G. (Zootaxa, 2004)
Brachypogon (Isohelea) borkenti, n. sp. from steppe areas of the Argentinean provinces of Mendoza and R o Negro is described and illustrated from male and female specimens collected by sweep net and Malaise trap. The species is compared with its congener B. hugoi Spinelli & Grogan, and a key to females and males of the six Neotropical species of the subgenus is included